The Maqashid of Sunnah in Hadith: A Critical Reinterpretation of The Repeated Hajj Phenomenon in Indonesia - Rahman, Andi; Nurhakim, Amien (Al-Bukhari : Jurnal Ilmu Hadis, 2024)
This article explores the phenomenon of repeated Hajj in Indonesia through the guideline of Maqashid Sunnah, intending to provide a critical reinterpretation of this practice. As one of the fundamental pillars of Islam, Hajj has deep spiritual and social significance. However, the trend of repeated Hajj in Indonesian society has raised various controversies, including social, economic, and religious implications. By employing a Maqashid Sunnah approach, this article intends to uncover the underlying objectives of Sharia behind the Hajj rituals as revealed in Hadiths. Furthermore, it explores the implications of this phenomenon on public understanding of Hajj and its religious values. The results show that the primary purpose of prescribing Hajj in Hadith is to ensure the maintenance of the Holy Land every year and to perform Hajj for every Muslim who has not yet done so. Prophet Muhammad (peace be upon him) performed Hajj only once during his lifetime, despite having the opportunity to perform it thrice in 8 AH, 9 AH, and 10 AH. For him, social welfare was prioritized over personal benefit, leading him to focus on disseminating Islamic teachings and providing sustenance to those in need, caring for orphans, and engaging in jihad for the sake of Allah. The findings of this analysis are expected to provide a broader understanding of the meaning of Hajj in Indonesian society and cultivate awareness of the importance of proper understanding of Maqashid Sunnah in religious practice.